KAJIAN YURIDIS FEMALE GENITAL MUTILATION (FGM) DALAM PERSPEKTIF HAK ASASI MANUSIA (Studi terhadap Praktik Female Genital Mutilation di Indonesia) - Rahayu, Elfia Farida, Marlinda Oktavia Erwanti, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
The position of female genital mutilation is in human rights perspective (both of international and Indonesia) should be a main element for making the regulation and policies in a practice of female genital mutilation that must be banned. It relates to the women's violation and based gender discrimination which is seen from the impact and implementation of female genital mutilation.Â This research uses a normative judicial approach, which is a legal research that is conducted by researching in library way or secondary data. Female genital mutilation that is viewed by human rights perspective. In fact, the impact and practice of female genital mutilation, has fulfilled the element of based gender discrimination and violence against women that cause physical, non physical and sexual abuse. Therefore, the international community and the government of Indonesia shouldÂ stop explicitly the practice of female genital mutilation, through legal action, make a binding rules and policies withÂ a gender perspective.